Diversity of formicidae in tropical dry forest at different temporal and spatial scales - Silva, Tatianne Gizelle Marques (2011)
Ecological processes influence species diversity at different spatial and temporal scales. Within each scale (spatial or temporal) different factors act on diversity depending on the size of the scales. For example, interactions between species (local spatial scale) and seasonality (large time scale). The purpose of this thesis was to investigate the ecological processes that determine the ant species richness in Tropical Dry Forest (TDFs) in different spatial and temporal scales. First we identified the ecological processes that govern the ant diversity in different time scales (ecological succession and seasonal variation), in order to understand the cause-effect patterns of diversity found in the study. Our results indicated an increase in the total richness of ant species in the later stages of succession. In the analysis of each microhabitat, the richness of arboreal and epigaeic ants did not change with the advancing of succession. However, the composition of ant communities of the two microhabitats differed among successional stages. For the hypogaeic microhabitat, the number of ant species was higher in intermediate and late stages of succession. The porosity of the soil and the richness of plant species explain this increase in species richness of hypogaeic ants. Moreover, the composition of hypogaeic ants also differed among the successional stages. Additionally, the total number of ant species was higher in the dry season and the composition of ant species did not change between seasons. Therefore, both the succession and the seasonality influence the ant species and richness in the TDFs. Finally, the second chapter of the thesis aims to determine whether there are nonrandom processes influencing the observed pattern of ant diversity, but also to determine at what scale these processes can be more influential. The additive partitioning of diversity was used to separate the regional ant diversity ( ) into components of diversity within ( ) and between ( ) samples. The spatial partitioning of ant species diversity distributed among the regions of Brazil shows that each collection point ( ) holds a mean diversity larger than the one expected by the null hypothesis. The (between fragments) and 3 diversities observed observed (between regions) were higher than expected by chance. Applying the partition analysis for each region separately, the diversities observed between fragments (TDF and surrounding areas) from all regions of Brazil were higher than the ones expected by the null hypothesis. The partition analysis helped us to identify the spatial boundaries, where the non-random processes must interact and differentiate disproportionately ant diversity. Therefore, based on species composition and diversity patterns that we found in our studies, we emphasize the importance of preserving the remaining and secondary areas of TDFs.